Sistem Informasi Akademik & e-Rapor Pengaruh terhadap Layanan Akademik dan Pelaporan - Sesi Ulul Azizah (GLOBAL SCIENTS PUBLISHER, 2026)
Digital transformation in educational administration has brought significant changes through the implementation of the Academic Information System (SIAKAD) and e-Report. The purpose of this study is to examine how the use of the system affects information on the quality of academic services and the accuracy of reporting learning outcomes at various levels of education. The method used is a Systematic Literature Review (SLR), which involves reviewing various research articles related to information technology integration, the development of web-based and mobile information systems. The results of the study indicate that digitizing academic services can improve operational efficiency, reduce human error—also known as human error—and make information clearer for students and parents. It is proven that the integration of features such as e-Report and real-time notifications accelerates the dissemination of student progress reports. However, data security aspects through encryption and user readiness for digital literacy determine the success of this system. The conclusion of this study confirms that an integrated academic information system is not only an administrative tool, but also an important foundation in improving the quality and credibility of educational services in the digital era.